2019
DOI: 10.21911/aai.414
|View full text |Cite
|
Sign up to set email alerts
|

Is There An Effect of Inhaled Steroid Treatment on Heart Rate?

Abstract: Objective: To evaluate the effect of inhaled steroids on the heart rate variability in pediatric patients with asthma. Materials and Methods: The study included 17 pediatric patients with asthma using inhaled steroids and a control group of 17 healthy, ageand gender-matched children. A 24-hour Holter monitor was applied and the time domain and frequency domain parameters of heart rate variability were examined. The values were obtained for night, day, and a 24 hour cycle. Results: No statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Regarding the R‐R interval, 4 of the 6 studies that included this variable 5,6,12,13 found lower values in the asthma group; only Rezvan et al 16 and Tokuyama et al 27 found higher values in the asthma group. In addition, 2 of the 4 studies found 5,12 demonstrated lower SDNN values in the asthma group. Regarding RMSSD, 5 of 6 studies 3,6,12,14,25 found higher values in the asthma group; only Rimes et al 26 found a lower value in the asthma group.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Regarding the R‐R interval, 4 of the 6 studies that included this variable 5,6,12,13 found lower values in the asthma group; only Rezvan et al 16 and Tokuyama et al 27 found higher values in the asthma group. In addition, 2 of the 4 studies found 5,12 demonstrated lower SDNN values in the asthma group. Regarding RMSSD, 5 of 6 studies 3,6,12,14,25 found higher values in the asthma group; only Rimes et al 26 found a lower value in the asthma group.…”
Section: Resultsmentioning
confidence: 97%
“…Regarding the methodological quality of the included studies, 5 4,5,14,16,24 were classified as high quality and 10 3,6,12,13,15,25–29 as moderate quality. Table 5 presents the topics assessed in the AHRQ scale.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations